Artificial iron hydrogenase made by covalent grafting of Knölker's complex into xylanase: Application in asymmetric hydrogenation of an aryl ketone in water. (23rd May 2020) - Kariyawasam, Kalani; Ghattas, Wadih; De Los Santos, Yossef López; Doucet, Nicolas; Gaillard, Sylvain; Renaud, Jean‐Luc; Avenier, Frédéric; Mahy, Jean‐Pierre; Ricoux, Rémy
Abstract: We report a new artificial hydrogenase made by covalent anchoring of the iron Knölker's complex to a xylanase S212C variant. This artificial metalloenzyme was found to be able to catalyze efficiently the transfer hydrogenation of the benchmark substrate trifluoroacetophenone by sodium formate in water, yielding the corresponding secondary alcohol as a racemic. The reaction proceeded more than threefold faster with the XlnS212CK biohybrid than with the Knölker's complex alone. In addition, efficient conversion of trifluoroacetophenone to its corresponding alcohol was reached within 60 H with XlnS212CK, whereas a ≈2.5‐fold lower conversion was observed with Knölker's complex alone as catalyst. Moreover, the data were rationalized with a computational strategy suggesting the key factors of the selectivity. These results suggested that the Knölker's complex was most likely flexible and could experience free rotational reorientation within the active‐site pocket of Xln A, allowing it to access the subsite pocket populated by trifluoroacetophenone. Abstract : The covalent attachment of a Knölker's complex to a S212C xylanase mutant afforded a new Artificial iron hydrogenase that was found able to catalyze the hydrogenation of trifluoroacetophenone in water